PROSEDUR PEMBENTUKAN PERJANJIAN INTERNASIONAL MENURUT VCLT 1969 DAN UNDANG-UNDANG NOMOR 24 TAHUN 2000 TENTANG PERJANJIAN INTERNASIONAL - Azra Yuniar Fajriani; Zahra Herwannuri (Jurnal Riset Multidisiplin Edukasi, 2026)
International treaties are the primary legal instruments governing relations between states in the modern international order. Their formation process cannot be separated from two crucial aspects, namely the instruments of state representative authority in the form of Full Powers and Credentials, as well as the procedural stages that must be passed until an agreement has binding force. This study aims to examine the regulation of Full Powers and Credentials and the stages of formation of international treaties comparatively between the Vienna Convention on the Law of Treaties (VCLT) 1969 and Law Number 24 of 2000 concerning International Treaties. The method used is normative juridical with analytical descriptive specifications through literature studies of primary, secondary, and tertiary legal materials. The results of the study indicate that Full Powers and Credentials are two substantially different instruments, where Full Powers provide legal authority that directly binds the state while Credentials are only limited to the legitimacy of presence and negotiation. In addition, there are similarities and differences between the stages of formation of international treaties in the VCLT 1969 and Law No. 24 of 2000, particularly regarding the mechanism for ratification and enforcement of agreements that are adapted to the Indonesian constitutional system.